STRATEGI PELESTARIAN KEBUDAYAAN ACEH DI MASYARAKAT KOTA BANDA ACEH - Muklis, Muklis; Emsa, Tasmiati; Zulfikar, Zulfikar (Jurnal Sosial Humaniora Sigli, 2024)
This research aims to identify strategies for preserving Acehnese culture in the Banda Aceh City community which is the work area of the Banda Aceh City Education and Culture Office and describe the efforts made to develop cultural preservation strategies in the Banda Aceh City community so that they are in accordance with valid and accurate cultural data. The method used is descriptive qualitative by relatively trying to maintain the integrity of the object under study. The conclusion of this research is that the cultural strategy did not work well because the implementation time was delayed due to COVID-19. Nearly all 2020–2022 programs and budgets were changed to address COVID-19. and using cultural strategies to create cultural potential maps and provide cultural facilities and infrastructure. In Banda Aceh City, the cultural potential map includes cultural heritage sites, historical moments, museums, and several graves of Acehnese heroes and high-ranking officials. However, the lack of facilities and infrastructure is still a problem in the cultural preservation process. The work program of the Banda Aceh City Education and Culture Office meets the standards of Indonesian cultural progress. However, there are still many problems faced in implementation, such as a lack of budget, facilities, and suggestions. To adjust to the available budget after the COVID-19 pandemic, the Banda Aceh City Education and Culture Office must restructure the work program according to the available budget in the long term. short (5 years). Apart from that, it is necessary to update the regional potential map so that there will be more culture in Aceh. This will increase the opinion of the local community about the cultural potential of the region. The Banda Aceh City Education and Culture Office must continue to develop programs.Keywords : Strategy, Preservation, Culture, Aceh